The destination and local brand equity role in shaping tourist’s loyalty: the moderated mediation effect of age and number of visits - Reem Mohamed Elalfy; Ahmed Elgazzar; Youssra Y. El-Ashry; Mohamed H. Elsharnouby (Future Business Journal)
Abstract The current study adopts a unique approach in investigating the effect of destination brand equity and local brand equity on destination brand loyalty and local brand loyalty. It examines the direct influence of both destination brand equity and local brand equity on brand loyalty, as well as the mediation role of destination brand loyalty in these relationships. Furthermore, it delves into the moderated moderation effect of age and number of visits, providing a comprehensive understanding of the complex relationships in destination marketing. A survey approach was adopted. Two hundred and fifty-four valid questionnaires were analysed. A self-administered questionnaire was adopted to collect data from tourists who visited Egypt via an online survey. The results underscore the significant influences of destination equity on both destination loyalty and local brand loyalty. They also highlight the positive effects of local brand equity on destination loyalty and local brand loyalty. The results also show that destination loyalty has a positive influence on local brand loyalty. The executives and marketers in the country’s institutions (e.g. ministry of tourism) and brands should increase their efforts towards enhancing the destination equity and local brand equity. Finally, the effect of destination equity on local brand loyalty, through destination loyalty, is more pronounced when the tourist’s age is younger, rather than being older. Therefore, practitioners and marketers should focus on younger tourists when they develop the campaigns and activities about the destination and local brands.